55th AIAA Aerospace Sciences Meeting 2017
DOI: 10.2514/6.2017-0148
|View full text |Cite
|
Sign up to set email alerts
|

Spray Characteristics and Flame Structure of Jet A and Alternative Jet Fuels

Abstract: A 2D phase Doppler anemometer is used to characterize alternative jet fuel droplets and compare them to Jet A fuel droplets in the National Jet Fuel Combustion Program referee single cup combustor near lean blowout. The two alternative jet fuels selected were chosen for their unusual properties: one with low cetane number and one with a flat boiling curve. Measurements are made on all three fuels at steady-state combustion at a pressure of 30 psia, swirler pressure drop of 3 percent, and a global equivalence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…This observation probably deserves to be further investigated. Experiments with different fuels in a single-cup swirl-stabilized combustor at steady-state combustion conditions [38], also revealed minimal axial velocity differences for the fuels tested, whereas, contrary to the present results, velocity measurements, in a spray produced by a pressure swirl nozzle [19], were lower for Jet A-1 fuel (having the largest kinematic viscosity) than for the other fuels tested and the differences became larger as the injection pressure was increased.…”
Section: Axial Droplet Velocitycontrasting
confidence: 55%
See 1 more Smart Citation
“…This observation probably deserves to be further investigated. Experiments with different fuels in a single-cup swirl-stabilized combustor at steady-state combustion conditions [38], also revealed minimal axial velocity differences for the fuels tested, whereas, contrary to the present results, velocity measurements, in a spray produced by a pressure swirl nozzle [19], were lower for Jet A-1 fuel (having the largest kinematic viscosity) than for the other fuels tested and the differences became larger as the injection pressure was increased.…”
Section: Axial Droplet Velocitycontrasting
confidence: 55%
“…On the other hand, measurements in sprays produced by a hybrid airblast atomizer in [23], present compatible results with the present study, indicating also a small decrease in diameter for higher injection pressure. However, experiments with the same fuels as in [23], in a single-cup swirl-stabilized combustor at steady-state combustion conditions [38], present an almost inverse relation between fuel properties and droplet sizes. It has to be noted that contrary to the above-mentioned investigations [23,38], where the droplet size histograms were skewed, in the present work the size histograms (typical samples are provided as supplementary materials, Figures S1 and S2) have, in most cases (independent of blend, pressure or location), a rather symmetric form of similar extent.…”
Section: Sauter Mean Droplet Diametersmentioning
confidence: 99%
“…To investigate in detail the influence of different fuels (e.g. Jet A-1, Fischer-Tropsch Fuels) on the combustor performance, generic experiments have been successfully developed and used ( [5][6][7]). Furthermore, for the development of fuel-dependent models, unit test experiments have been beneficially used (e.g.…”
Section: Fig 1 Approval Processing Pathway Of New Aviation Turbine Fmentioning
confidence: 99%
“…The ambient conditions inside the facility were maintained at 204 kPa and 394 K, and the fuel was delivered at 322 K. The nozzle pressure differential was noted to impact the droplet size substantially. Mayhew et al [18] performed a similar study on NJFCP fuels in a combustion environment and reported that the fuel volatilization properties influenced the droplet sizes for the conditions studied. In both studies [17,18], spray measurements were conducted at constant pressure (ambient) and temperature (ambient, fuel).…”
Section: Introductionmentioning
confidence: 98%